Question

Watch Video

Show Examples
Given g, of, x, equals, minus, x, minus, 4g(x)=−x−4, find g, of, minus, 4g(−4).

1 answer

To find g(−4), we substitute x with −4 in the given equation g(x) = −x−4:

g(−4) = −(−4) − 4 = 4 − 4 = 0

Therefore, g(−4) = 0.

Now, to find g of minus 4g(−4), we substitute the value of g(−4) into the equation:

g(−4) = 0
g(−4) = -4(0) = 0

Therefore, g of minus 4g(−4) = g(0) = -0 - 4 = -4.
Similar Questions
  1. QuestionWatch Video Show Examples Solve the system of equations 4, x, minus, 7, y, equals, minus, 44x−7y=−4 and x, minus, y,
    1. answers icon 1 answer
  2. QuestionWatch Video Show Examples Solve the system by substitution. y, equals, minus, 2, x y= −2x y, equals, minus, 9, x,
    1. answers icon 1 answer
  3. QuestionWatch Video Show Examples Find the value of xx in the equation below. 12, point, 2, equals, x, minus, 12, point, 3 12.2=
    1. answers icon 1 answer
  4. QuestionWatch Video Show Examples Solve for xx and graph the solution on the number line below. minus, 7, is less than, minus,
    1. answers icon 1 answer
more similar questions